Metagenomic evidence for antibiotics-driven co-evolution of microbial community, resistome and mobilome in hospital sewage. (15th June 2023) - Sun, Jiayu; Yuan, Yumeng; Cai, Leshan; Zeng, Mi; Li, Xin; Yao, Fen; Chen, Weidong; Huang, Yuanchun; Shafiq, Muhammad; Xie, Qingdong; Zhang, Qiaoxin; Wong, Naikei; et al.
Abstract: Overconsumption of antibiotics is an immediate cause for the emergence of antimicrobial resistance (AMR) and antibiotic resistant bacteria (ARB), though its environmental impact remains inadequately clarified. There is an urgent need to dissect the complex links underpinning the dynamic co-evolution of ARB and their resistome and mobilome in hospital sewage. Metagenomic and bioinformatic methods were employed to analyze the microbial community, resistome and mobilome in hospital sewage, in relation to data on clinical antibiotic use collected from a tertiary-care hospital. In this study, resistome (1, 568 antibiotic resistance genes, ARGs, corresponding to 29 antibiotic types/subtypes) and mobilome (247 types of mobile genetic elements, MGEs) were identified. Networks connecting co-occurring ARGs with MGEs encompass 176 nodes and 578 edges, in which over 19 types of ARGs had significant correlations with MGEs. Prescribed dosage and time-dependent antibiotic consumption were associated with the abundance and distributions of ARGs, and conjugative transfer of ARGs via MGEs. Variation partitioning analyses show that effects of conjugative transfer were most likely the main contributors to transient propagation and persistence of AMR. We have presented the first evidence supporting idea that use of clinical antibiotics is a potent driving force for the development of co-evolving resistome and mobilome, which in turn supports the growth and evolution of ARB in hospital sewage. The use of clinical antibiotics calls for greater attention in antibiotic stewardship and management. Graphical abstract: Image 1 Highlights: Clinical use of antibiotics had lasting effects on ARGs and MGEs distribution in hospital sewage. 4, 452 bacterial species, 1, 568 ARGs, 247 MGEs were form complex networks in hospital sewage. Effects of conjugative transfer were the main contributors to propagation of AMR by VPA analyses.